The bZIP transcription factor CibZIP43 positively regulates salt and heat tolerance in pecan (Carya illinoinensis) - Linna Wang; Nianqing Jiang; Lina Zou; Jinhua He; Zixian Yao; Shunran Zhang; Yan Xiang (BMC Plant Biology)
Abstract Pecan (Carya illinoinensis) is an economically and ecologically important tree species, but its growth is frequently challenged by salt stress and heat stress. bZIP transcription factors are key regulators of plant responses to abiotic stresses. This study aimed to functionally characterize the pecan transcription factor CibZIP43 and reveal its role in salt and heat stress tolerance. The CibZIP43 gene was overexpressed in Arabidopsis, and the results showed that CibZIP43 overexpression (OE) in Arabidopsis significantly enhanced the tolerance of transgenic plants to salt and heat stress. Physiological and biochemical analyzes showed that CibZIP43 OE lines exhibited better growth and improved physiological indices under salt and heat stress, including increased chlorophyll content, relative water content, and antioxidant enzyme activities, along with reduced membrane lipid peroxidation and proline accumulation. Moreover, CibZIP43 OE enhanced plant adaptation to salt and heat stress by regulating the expression of Na+/K+ transporter-related and heat stress-related genes. These findings uncover new molecular mechanisms and provide potential genetic resources for breeding for stress-tolerance in pecan varieties.